The The Efficacy of Herbal Extract on Osteoarthritis Treatment: A Meta-Analysis - Pramesty Purborini, Gendis; Budi Deskianditya, Resa; Bahar, Yeni; Septianawati, Paramita (Riviera Publishing, 2025)
Osteoarthritis (OA) is characterized by pathology involving the entire joint, including cartilage degradation, osteophyte formation, and synovial inflammation, leading to pain, stiffness, and loss of normal joint function. Data on the incidence and prevalence of osteoarthritis in general, estimated at 302 million people worldwide. In indonesia there is an increase in cases of osteoarthritis in 2019 occurred by 153,2% in male population and 143,36% infemale population. This study aims to provide an evidence-based review of the efficacy of herbal extracts as an adjunctive or alternative therapy in the treatment of osteoarthritis. The search results were 746 studies, only 9 studies met the inclusion criteria. From the use of herbal extract combination of tamarindus indica and curcuma longa (turmeric), boswellia serrata, and zingiber officinale. The results obtained showed that the combination of curcuma longa (turmeric) and tamarindus indica showed a significant value which can be seen from the meta-analysis results of -9.72 (95% CI -15.52, -3.92) for the use of extracts for 5 days and -15.66 (95% CI -21.21, -10.11) for the use of extracts for 28-30 days, indicating that the combination of tamarindus indica and curcuma longa has potential as a long-term or short-term osteoarthritis therapy